(untitled) (Global Journal of Human-Social Science, 2018)
Since independence in 1971, Bangladesh has endured almost 200 disaster events storm surges, floods, tornadoes, earthquakes, droughts and other calamities. The cyclone Sidr is the superset cyclone in Bangladesh. The study has been conducted at Hizla Upazila in the Barisal district of Bangladesh. Natural disasters are increasing day by day according to the the study. The local government does not act systematically as per government rules. Damage and losses assessment was not systematic according to standing orders on disaster. The dwellers of the study area continue their livelihoods very miserable after Sidr. The farmer lost their all crops and crops value was 45,75,362 dollar. The fisherman lost their net, fish and boat and their wealth value was 35735 dollar. 39 education institution fully and 66 education institution parti cannot recover properly from their losses. Some national or international NGO and Bangladesh government provided relief like dry foods, seeds, fertilizer, rice and old clothes etc. Relief was not sufficient for the dwellers in the study area. The study area has no Disaster Management Committee or no Red Crescent members to recover from the impacts of natural hazards during the disaster period